ANALISIS USAHA DAN SALURAN PEMASARAN TERI KRISPI DI KABUPATEN BELITUNG - burhanudin1 burhan; Kurniawan Salim; Endang Bidayani (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2020)
Anchovies is one of the diversification products (product diversity) of anchovy. The research objective was to analyze the anchovies production business and to analyze the marketing channels of crispy anchovies production in Belitung Regency.This research was conducted in May-June 2019 in Belitung Regency. The method used is descriptive method. The data obtained are revenue, income, profit, B / C Ratio, Break Even Point, Net Present Value (NPV) and Return On Investment (ROI) of anchovies marketing channel. Based on the results of the study, anchovy used is a type of black anchovy (Stolephorus commersonii) using a boat chart fishing gear. The crispy anchovy product in Belitung Regency has eligibility criteria with a PBP value of 0.52 years, NPV of IDR 1,401,926,475, B / C ratio of 1.94, and ROI of 98%, BEP of product 7,842 kg and BEP of receipt of IDR. 784,214,786. The average NPV value is IDR 1,451,926,475 and the average B / C ratio of entrepreneurs is 1.94. The NPV and BCR values ​​are> 1, so the anchovies business in Belitung Regency is feasible to be implemented. There are 2 types of marketing channels for anchovies in Belitung Regency, namely: 1. Producers - end consumers and, 2. Producers - big traders - end consumers.